Bioactivities of Proctolin Mimetic in Drosophila melanogaster - Brunkow, Jenna; Fatehi, Soheila; Park, Yoonseong (My University, 2018)
The insect neuropeptide proctolin was originally purified for its myotropic actions on insect hindguts, however it has been shown to be distributed widely throughout arthropods. This pentapeptide, RYLPT or Arg-Tyr-Leu-Pro-Thr, is highly conserved across arthropod species. We were interested in whether observable bioactivity, physiological and behavioral changes, occurs upon the injections of proctolin or proctolin mimetic peptides. We found strong activities of proctolin and proctolin mimetic in immediate inductions of proboscis behavior and defecation. Peptidomimetics showed strong activities opening a new revenue for development of new class of insecticidal compound.
Keywords: Fall 2018